El guamúchil Pithecellobium dulce (Roxb.) Benth, un ejemplo de uso múltiple - Monroy, Rafael; Colín, Hortensia (Instituto de Ecología, A.C., 2016)
Dry deciduous forest multipurpose trees result of particular interest because of their potential contribution to solve socioenvironmental problems. This is the case of guamúchil (Pithecellobium dulce) , a multipurpose tree that is used as live fence in cultivated lands. This work was made in Xochitepec, Morelos, located in Cuernavaca's metropolitan area, especially in cultivated lands which have resisted the advance of urbanization. The work was conducted in order to find out what is the knowledge of the countryside people about guamúchil. Traditional knowledge systematization about guamúchil was made as a way to preserve this tree and the culture related in an area of urban growth. The information was gathered by ethnobotanical interviews to the countryside people. Moreover, ecological parameters were calculated in the arboreal community of the live fence. Six utilitarian values were registered, medicinal and wood being the most important. Almost all the guamuchil's vegetal structures are used. Guamúchil was the species with the most important ecological value in the live fences, followed by colorin. Ecological and use values of guamúchil have resulted of the relation between society and nature.